(untitled) (Journal of Fatima Jinnah Medical University, 2026)
Introduction: Zinc is an important cofactor in ammonia metabolism in the liver and in the regulation of cognitive functions. Deficiency of this trace mineral is common in patients with advanced hepatic disease, and has been blamed for hepatic encephalopathy (HE) degeneration. The current study determined the effect of 12 weeks of oral zinc supplementation on serum zinc concentrations in patients with liver cirrhosis. Methods: This single-center, prospective, pre-post interventional study was conducted at Ghurki Trust Teaching Hospital, Lahore, from July to December 2025. A total of 240 cirrhotic individuals (Child-Pugh class B-C) were recruited for this study. The patients received oral zinc sulfate (50 mg) twice daily up to 12 weeks and underwent follow-up to assess improve-ment in zinc levels and the grade of hepatic encephalopathy. Serum zinc levels were measured by atomic absorption spec-troscopy at baseline and after 12 weeks of supplementation. Results: The study participants had significantly lower serum zinc levels (mean, 37 ± 10 µg/dL) and higher plasma ammo-nia levels (mean, 85 ± 20 mmol/L) at baseline. Among them, 20.8% (n=50) had West Haven grades III, and 20.8% (n = 50) had grade IV, while the rest fell into grades I-II. There was a significant elevation in mean serum zinc levels (78 + 15 µg/dL; p<0.001), accompanied by a reduction in mean ammonia levels (60 + 18 μmol/L; p<0.001) after Zinc supplementa-tion. There was a significant increase in the proportion of the participants with no or minimal HE (grade I) from 12.5% to 41.7% (p<0.01). On the contrary, the number of participants with severe HE (grade IV) decreased from 20.8 to 8.3 percent. Conclusion: Zinc supplementation in cirrhosis significantly reduces ammonia concentrations and is associated with an overall improvement in HE grading.